Analysis of Mathematics Curricula in the Faculties of Education of Peruvian Universities - López Rengifo, Carlos Fernando (2021)
The following article is based on an analysis of the curricula of the mathematics specialty, of education faculties, corresponding to five Peruvian universities. To this end, the differences and similarities that exist in said curricula were established, responding to the following questions: are vocational training curricula relevant to the real demands of educational institutions? How do they operationalize the competency approach in said curricula? Do the curricula respond to the profiles of the graduate? For this, the curricular components were studied: purposes, contents, methodology and evaluation; under the mixed approach, and with the appropriate scientific approach, using as specific methods: descriptive and discursive analysis; those that yielded, among others, the following results: a) Work by competencies is assumed in a procedural way, which results in different ways of applying it. b) The dosage of credits in the disciplinary, didactic and research areas differ significantly.